Performance increase of tandem amorphous/microcrystalline Si PV devices under variable illumination and temperature conditions. (September 2018) - Ricco Galluzzo, F.; Scuto, A.; Gerardi, C.; Battaglia, A.; Canino, A.; Lombardo, S.
Abstract: Wear out in the maximum power point condition of tandem microcrystalline Si/amorphous Si thin film PV modules due to extended light soaking is a well-known effect due to the Staebler–Wronski mechanism [1 ]. However, several studies [2–8 ] on a-Si:H single junction and tandem solar cells, have shown that, under suitable conditions of electric field in reverse bias, illumination, especially at well-defined wavelengths (700–800 nm), and temperature conditions, an improvement of the cell main electric parameters is possible. In this work, we report on new stress tests performed on tandem amorphous Silicon PV devices (both non-stabilized and stabilized), highlighting the improvement of their electrical performances, founded both in the tests performed on non-stabilized samples (essentially due to the reverse bias stresses carried out in these tests) and in the outdoor tests on stabilized samples (not subjected to reverse bias stresses) going from morning to afternoon illumination. In the latter tests, the efficiency improvement observed in the afternoon is stable overnight and observed also in the early stages of the morning outdoor test in the following day. Possible causes of such effect are discussed. Highlights: The results shown of stress tests on tandem amorphous Si PV modules highlight relevant improvements of the electrical performances of such devices, both on non-stabilized samples and on stabilized ones (i.e. subjected to an extended light soaking for 1000 h, before our stress tests). The tests performed on non-stabilized samples (both outdoor and indoor) allowed to observe significant overall conversion efficiency increases attributable to the reverse bias stress conditions applied to samples of three different groups (respect to the sample hired as ref. module for each of these groups), according to the benefits observed in our previous indoor tests on a-Si:H-based solar cells subjected to light assisted reverse bias stresses. The outdoor tests performed on stabilized samples show electric performances improvements in the afternoon, as a systematic effect, whose cause is still studied, but it may be due to an effect triggered by the combination of two factors: the NIR illumination and a thermal heating (at low temperatures) of the samples tested.